Pengaruh Faktor Penggunaan E-Marketing terhadap Kepuasan Pelanggan pada Hartanimart.Com - Aminudin, Iwan; Muttaqien, Ihsanul; Ruminta, Darkiman (www.bsi.ac.id, 2022)
Abstract – Advances in internet-based communication and information technology, in the digital era bring major changes in various aspects of life, so that agribusiness actors are also competing to create a digital marketing system in order to maintain or improve the sustainability of their business. This study aims to analyze the factors that influence the use of e-marketing on consumer satisfaction at Hartanimart.com. The research approach is descriptive quantitative, through survey activities with descriptive tabulation methods and PLS-SEM data analysis processed with the help of Excel 2010 software and Smart PLS software version 3.2.1. The findings show that of the 3 hypotheses tested there are 3 accepted/proven hypotheses based on the value (t-test > 1.96) and value (p-value < 0.05), namely H1 = usefulness, H2 = ease of use, H4 = norm subjective influence significantly on the use of e-marketing on online transaction activities at Hartani Farm. Other hypotheses were rejected such as H3 = attitude of use has a significant effect on the use of e-marketing on online transaction activities at Hartani Farm and H5 = factors of e-marketing users have a direct and indirect effect on the level of consumer satisfaction on online transaction activities at Hartani Farm. This indicates that Hartani Farm consumers directly or indirectly do not feel satisfaction from the factor of using e-marketing. While the subjective norm factor has a direct influence on consumer satisfaction. For this reason, the management of the Hartani Farm company must be more creative in finding other ways or breakthroughs in its marketing program activities so that more consumers buy their products and win business competition in the future.Keywords : Customer Satisfaction, Use of e-marketing